Successful treatment of severe immune checkpoint inhibitor associated autoimmune hepatitis with basiliximab: a case report - Zarrabi, Maiah; Hamilton, Camille; French, Samuel W.; Federman, Noah; Nowicki, Theodore S. (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) targeting programmed cell death-1 (PD-1) and its corresponding ligand PD-L1 are being increasingly used for a wide variety of cancers, including refractory sarcomas. Autoimmune hepatitis is a known side effect of ICIs, and is typically managed with broad, non-specific immunosuppression. Here, we report a case of severe autoimmune hepatitis occurring after anti-PD-1 therapy with nivolumab in a patient with osteosarcoma. Following prolonged unsuccessful treatment with intravenous immunoglobulin, steroids, everolimus, tacrolimus, mycophenolate, and anti-thymoglobulin, the patient was eventually treated with the anti-CD25 monoclonal antibody basiliximab. This resulted in prompt, sustained resolution of her hepatitis without significant side effects. Our case demonstrates that basiliximab may be an effective therapy for steroid-refractory severe ICI-associated hepatitis.